The Probable Impact of Global Change on the Water Resources of Patagonia, Argentina - Quintela, R. M. (1996)
Very little work has been undertaken on the hydrological impact of global warming in South America. In this study, some initial estimates are made using IPCC and Hadley Centre scenarios, supported by an analysis of long-term trends in rainfall patterns. Under the global warming scenarios, we expect a drying trend in the north of Argentina and a wetter climate in the south, accompanied by a reduced meridional temperature gradient. Snowlines are likely to rise, although the overall response of glaciers needs detailed investigation. However, analyses of rainfall records suggest that rainfall has been increasing in the north, contrary to the expected global warming pattern.